2018
DOI: 10.1186/s12891-018-2005-y
|View full text |Cite
|
Sign up to set email alerts
|

Identifying complications requiring re-operation following primary hip or knee arthroplasty: a consecutive series of 98 patients

Abstract: BackgroundThe number of hip and knee arthroplasties completed is expected to double over the next decade. In public hospitals, regular post-arthroplasty orthopaedic review has commonly occurred for the duration of a patient’s life, which requires substantial outpatient resources. However, there is limited evidence regarding the utility of these reviews for identifying complications. The current study investigated when and where complications requiring re-operation were identified following primary hip or knee … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…We observed that many individuals travelled long distances for primary joint replacement procedures. This underpins need for new/novel models or care and review of these patients' travel burden, perhaps using high-quality data registries, as previously described [30,31]. Many of the joint replacement procedures were performed in hospitals located within the three most populous LGAs of Ballarat, Greater Geelong and Warrnambool (n = 6485, 75.7% of all replacements).…”
Section: Discussionmentioning
confidence: 99%
“…We observed that many individuals travelled long distances for primary joint replacement procedures. This underpins need for new/novel models or care and review of these patients' travel burden, perhaps using high-quality data registries, as previously described [30,31]. Many of the joint replacement procedures were performed in hospitals located within the three most populous LGAs of Ballarat, Greater Geelong and Warrnambool (n = 6485, 75.7% of all replacements).…”
Section: Discussionmentioning
confidence: 99%
“…Ten orthopaedic surgeons complete TKAs at the hospital, of whom nine also perform sim‐BTKA. In 2015, 166 primary knee replacements were conducted at UHG, of which 16 (eight patients) were sim‐BTKAs …”
Section: Methodsmentioning
confidence: 99%